Transformation of Transitional Elements with Muqarnas from Early Ottoman Period to Classical Ottoman Period - Senalp, Hudai Sirri; Binan, Can Sakir (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2024)
Since the beginning of the Ottoman era, muqarnas have been incorporated into building designs. Along with advances in construction techniques, muqarnas were used structurally in the construction of mosques, baths, madrasahs and palaces as a means of transition to the dome. From the 14th century during the early Ottoman period, the Timurtas Pasha Mosque in Bursa (1379-92) and the Iznik Green Mosque (1378-91) were built with a focus on maintaining visual structural integrity within interior spaces. This was a common practice that persisted until the mid 18th century. While muqarnas can reinforce the visual integrity of a building as a transitional element, in some cases it can also transfer the weight of the dome to the walls and strengthen the building's structure when designed in the form of pendentives and squinches. It is important to note this duality in the use of muqarnas in the construction of buildings. The muqarnas utilised in the interiors during this period had a brick base, hidden by plaster on the outside. Many monumental buildings display this aspect of muqarnas, which requires expertise, particularly during restoration. Very little research has been conducted in this field. In the study, the transitional elements to the muqarnas dome, starting from the early Ottoman Period, will be examined until the Classical Ottoman Period, and the formal analysis between the 14th and 16th centuries will be made to understand the nature of the change it showed. After the literature review It is aimed to reach a synthesis with the inferences made through field research based on outputs.
Keywords: Early Ottoman period; Classical Ottoman period; Muqarnas; restoration; Transitional zone; Architecture